H(x)=1-1/3x

Simple and best practice solution for H(x)=1-1/3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for H(x)=1-1/3x equation:



(H)=1-1/3H
We move all terms to the left:
(H)-(1-1/3H)=0
Domain of the equation: 3H)!=0
H!=0/1
H!=0
H∈R
We add all the numbers together, and all the variables
H-(-1/3H+1)=0
We get rid of parentheses
H+1/3H-1=0
We multiply all the terms by the denominator
H*3H-1*3H+1=0
Wy multiply elements
3H^2-3H+1=0
a = 3; b = -3; c = +1;
Δ = b2-4ac
Δ = -32-4·3·1
Δ = -3
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 5x*8=2x+5 | | 16x+2(x+5)=x+5 | | Y=23/4x+92 | | 10p-60=4p | | 10p–60=4p | | 4x-2x=5=24-2x+5-8x | | 9+b2=58 | | 4a•6=72 | | -157=-6(-3p+3)+5 | | 3(t+4)-2(2t+3=4 | | -157=-6(-3p+3)=5 | | t²-2t=0 | | 5n+10n=75 | | G(n)=n(n)-3n | | 3-(-5x+4)=2(x-1)-8 | | 2x-8=3x-36 | | -5(3m+6)=-2(4m-2 | | 5(x+1)=5(x+3) | | 8x–1=63 | | 7(1-y0)=-3(y-2) | | k8/3=-2 | | (4x-2)=8x+22 | | 12d+40=1000 | | 10(2)^5x=-86 | | 16/5=-p-3/5p | | 0.006v=-0.135 | | -(z)=3.2 | | j−2=1 | | -7(1+7x)-6=134 | | -3.7x=7.77 | | 5x-14+x=20 | | 3(4n-1)-7n=17 |

Equations solver categories